Sporicidal Activity of Peracetic Acid and β-Propiolactone at Subzero Temperatures - Jones, Lynwood A. (1967)
A method was developed to evaluate and measure the sporicidal activity of peracetic acid (PAA) and β-propiolactone (BPL) at subzero temperatures as low as -40 C. Bacillus subtilis var. niger spores were used as the test organism. Both PAA and BPL were sporicidal at low temperatures, with PAA the more active. The temperature coefficients of the two chemicals are generally low over a range of 20 to -20 C, but increase significantly at temperatures below this. Results showed an initial lag in the PAA death rates that was directly dependent on the temperature. BPL did not show this lag time.